2018
DOI: 10.1088/1361-6455/aa9c36
|View full text |Cite
|
Sign up to set email alerts
|

Peculiarities of the coherent population trapping resonance in the fluorescence obtained in a coated87Rb cell in the presence of transverse magnetic field: theory and experiment

Abstract: We present an experimental and theoretical investigation of the influence of the transverse magnetic field (TMF) on the coherent population trapping resonances obtained on the Zeeman sublevels of the D 1 line of 87 Rb in a paraffin-coated vacuum cell. It is shown that a TMF changes the shape and sign of the resonance or destroys it completely. The role of the different rank polarization moments in the integral registered fluorescent signal in the presence of stray magnetic fields is clarified using numerical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…When the sample is situated in the XZand the YZ-planes, it causes a rather homogeneous MF along 0Z and a far smaller gradient along the 0X and 0Y-axis. The difference of the resonance widths is also due to the variation of the radial field created in the three sample positions [9,10]. When using miniaturized cells with alkali metal vapors, the situation changes and the recorded values of the magnetic field will characterize the sample locally.…”
Section: Resultsmentioning
confidence: 99%
“…When the sample is situated in the XZand the YZ-planes, it causes a rather homogeneous MF along 0Z and a far smaller gradient along the 0X and 0Y-axis. The difference of the resonance widths is also due to the variation of the radial field created in the three sample positions [9,10]. When using miniaturized cells with alkali metal vapors, the situation changes and the recorded values of the magnetic field will characterize the sample locally.…”
Section: Resultsmentioning
confidence: 99%
“…Второй член уравнения (1) описывает перенос заселенности и зеемановской когерентности с верхнего уровня ( f ) на нижний (ϕ) со скоростью Ŵ κ f ϕ за счет спонтанного испускания. Согласно [26] и с учетом нормировки Дьяконова для неприводимых тензорных операторов [36] имеем:…”
Section: теоретическое описание и модификация разреженной матрицы сисunclassified
“…The light-induced atomic coherence allows us to observe a nonlinear magneto-optical resonance (Hanle * Author to whom any correspondence should be addressed. resonance) as a function of scanning magnetic field, either by measuring the light transmission [5] or absorption [7] through the atomic medium. Depending on the hyperfine angular momentum of ground (F g ) and excited (F e ) states of the atomic medium, generally, two types of Hanle resonances are observed: dark (F g ⩾ F e ) and bright (F g < F e ) resonances [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, several groups have shown that the splitting of the Hanle resonance can occur with or without buffer gas collisions using an elliptically polarized light [16,23] and a linearly polarized light consisting of π-polarization [7,17,20,24]. With a π-polarized light, no Hanle resonance signal is obtained in the absence of TMF [20].…”
Section: Introductionmentioning
confidence: 99%